2002
DOI: 10.1073/pnas.052023599
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity-dependent membrane traffic at the neuromuscular junction

Abstract: During development and also in adulthood, synaptic connections are modulated by neuronal activity. To follow such modifications in vivo, new genetic tools are designed. The nontoxic C-terminal fragment of tetanus toxin (TTC) fused to a reporter gene such as LacZ retains the retrograde and transsynaptic transport abilities of the holotoxin itself. In this work, the hybrid protein is injected intramuscularly to analyze in vivo the mechanisms of intracellular and transneuronal traffics at the neuromuscular juncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
6

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 35 publications
2
22
0
6
Order By: Relevance
“…The transsynaptic trafficking of TTC fragment fusion proteins and WGA is known to be sensitive to presynaptic neuronal activity (Yoshihara et al, 1999;Miana-Mena et al, 2002). These tracers therefore can be used to reveal the presence of functional synapses between V1 INs and motor neurons.…”
Section: Generation and Analysis Of En1mentioning
confidence: 99%
See 1 more Smart Citation
“…The transsynaptic trafficking of TTC fragment fusion proteins and WGA is known to be sensitive to presynaptic neuronal activity (Yoshihara et al, 1999;Miana-Mena et al, 2002). These tracers therefore can be used to reveal the presence of functional synapses between V1 INs and motor neurons.…”
Section: Generation and Analysis Of En1mentioning
confidence: 99%
“…These tracers therefore can be used to reveal the presence of functional synapses between V1 INs and motor neurons. Although WGA also can be transported from postsynaptic dendrites to presynaptic axons, this route of transfer is very inefficient (Miana-Mena et al, 2002). Two complementary approaches were used to assess synaptic contacts between V1 INs and motor neurons: (1) transsynaptic labeling of motor neurons with a floxed WGA reporter mouse (Yoshihara et al, 1999; Y. Yoshihara, unpublished results) and (2) retrograde transsynaptic labeling of V1 INs from defined populations of motor neurons by the use of TTC fusion proteins (Coen et al, 1997).…”
Section: Generation and Analysis Of En1mentioning
confidence: 99%
“…TTC fusion protein lacks the translocation domain of native tetanus toxin, which is presumably required for cytosolic entry of tetanus neurotoxin to the cytosol [31]. In this respect, ß-gal-TTC protein injection studies have shown that the protein is never observed to be free in the lumen of vesicles or in the cytosol, its transport always being associated with membranes [32]. In the DNA injection study presented in this paper, the signal detected in the CNS was so weak that electron microscopy analyses of its subcellular location could not be performed.…”
Section: Discussionmentioning
confidence: 99%
“…The injection interval was chosen for two reasons: 1) to limit the exposure of the muscle to the protein in order to minimize potential direct effects on the muscle and 2) the hIGF-1-TTC fusion protein is detectable in the spinal cord for 21 days post-injection (Payne, et al, 2006). TTC was chosen as the carrier for hIGF-1 based on its rapid uptake from muscle and subsequent retrograde axonal delivery to spinal cord motor neurons (Coen, et al, 1997,Fishman and Carrigan, 1987,Fishman and Savitt, 1989,Miana-Mena, et al, 2002. Indeed, in a previous report, our laboratory has shown that the hIGF-1-TTC protein undergoes quick retrograde axonal transport to the spinal cord following intramuscular injection (Payne, et al, 2006).…”
Section: Animals and Injectionsmentioning
confidence: 99%